Contribution to the critical study of Cost Systems for ovine agricultural processes (Costos y Gestión, 2020)
The economic model traditionally used to evaluate costs and profitability in the agricultural sector has been theGross Margin per Hectare, a tool that comes from the field of agronomy and does not generate information onunit costs per production unit, marginal contributions, fixed costs, direct and indirect costs. Therefore, it doesnot allow the elaboration of Income Statements, breakeven analysis and other reports considered useful fordecision making. On the other hand, from the accounting discipline and in particular from Cost Accounting,various costing models and systems, applicable to industrial, commercial and service activities, have been generated, such as the cost system by processes, by orders or by activities. But it is difficult to find a modelapplicable to agricultural production processes, substantially different from those previously mentioned dueto its biological nature, in several cases self-reproductive and with frequent presence of the phenomenonof joint production, of which the sheep farming process is a good example. In the southern provinces ofArgentina or countries such as Uruguay, given the socio-economic relevance of livestock and agriculture,it is important that the group of rural sheep producers, and the professionals who advise them, have anaccounting model to support the process of decision making. Generating it is the goal of this proposal, as wellas promoting the discussion and critical analysis of the technical instruments available to our discipline today.
Keywords: sheep farming process; agricultural production processes; costs; gross margin per hectare; cost model; accounting model